1968
DOI: 10.1037/h0025267
|View full text |Cite
|
Sign up to set email alerts
|

The new psychophysics: Six models for magnitude estimation.

Abstract: 6 pictorial models describe the effect upon magnitude estimation of the choices of the values of the independent variables: (a) the range of stimuli, (b) whether the range includes the threshold region, (c) the position of the standard (1st stimulus) within the range, (d) the distance of the 1st variable (2nd stimulus) from the standard, (e) whether the set of numbers used is infinite or finite, and (f) the size of the modulus (the number given to the standard), (a) alone accounts for about J of the variance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
225
3
5

Year Published

1969
1969
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(250 citation statements)
references
References 66 publications
17
225
3
5
Order By: Relevance
“…Steps in this direction have been taken, e.g., by Mashhour (1961), Sjoberg (1965), Akesson (1966,1967), and Poulton (1968).…”
Section: Methodsmentioning
confidence: 99%
“…Steps in this direction have been taken, e.g., by Mashhour (1961), Sjoberg (1965), Akesson (1966,1967), and Poulton (1968).…”
Section: Methodsmentioning
confidence: 99%
“…(approximately 0 to 1.0 m/s 2 ), the power exponent was, of mathematical necessity (Laming, 1997), greater in the case of magnitude estimation since the subjective response values ranged from approximately 4 to 400, as opposed to the span of 0 to 10 for the CR-10. Poulton (1968) has suggested six factors that may influence the psychological processes involved in judging sensory magnitude. Of these, he suggested that the magnitude range of the stimulus accounted for up to 33% of the total variation in the power exponents.…”
Section: Discussionmentioning
confidence: 99%
“…The test participant is asked to assign numbers to the test stimuli such that the stimulus attribute of interest bears a ratio relationship with that of the reference. In magnitude estimation, it is known (Poulton, 1968) that the choice of the reference stimulus plays a role in determining the value of the power exponents that are obtained. For the set of 13 acceleration stimuli ranging from 0.01 to 0.86 m/s 2 in the current experiment, the median stimuli, which had an r.m.s.…”
Section: Procedures Of the Magnitude Estimation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A hipótese da amplitude dos estímulos Poulton (1968) deu outra interpretação muito diferente para o expoente da função de potência. A hipótese de Poulton é que este expoen-te não reflete o funcionamento dos diferentes sistemas sensoriais, mas somente certas características do experimento.…”
Section: José Aparecido Da Silva Nilton Pinto Ribeiro-filhounclassified